Safety and Feasibility of a First-Person View, Full-Body Interaction Game for Telerehabilitation Post-Stroke - Proffitt, Rachel; Warren, Jessica; Lange, Belinda; Chang, Chien-Yen (International Journal of Telerehabilitation, 2018)
This study explored the feasibility and safety of pairing the Microsoft Kinect® sensor with the Oculus Rift® Head Mounted Display (HMD) as a telerehabilitation technology platform for persons post-stroke. To test initial safety, fourteen participants without disabilities (age 30 ± 8.8 years) engaged in a game-based task using the Microsoft Kinect® with a first-person view using the Oculus Rift®. These tasks were repeated for five participants post-stroke (age 56 ± 3.0 years). No significant adverse events occurred in either study population. When using the Oculus Rift® HMD, three participants without disabilities reported dizziness and nausea. All of the participants post-stroke required hands-on assistance for balance and fall prevention. The intensive nature of physical support necessary for this type of interaction limits the application as a telerehabilitation intervention. Given the increasing availability of HMDs for commercial use, it is crucial that the safety of immersive games and technologies for telerehabilitation is fully explored.